O universo da cura na Capitania de Minas Gerais (1750-1808) - Grossi, Ramon Fernandes (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This article studies the everyday of medicine in Minas Gerais, Brasil, in the eighteen century, considering the questions was suggest by that reality, how the analyses of the presence of magic belief about cure and of the new techniques of medicine.